The Role of Sukuk Negara toward Financial Performance of Sharia Banking - Sholikha Oktavi Khalifaturofi'ah (LPPM of NAROTAMA UNIVERSITY, 2018)
ABSTRACT Purpose: This study aims to determine the extent of the influence of sukuk negara on financial performance, especially on profitability of sharia banking. Design/methodology/approach: This study begins with data collection from 2008 (the year in which sukuk negara is published) until 2016 by using panel regression method. Purposive sampling was used as sampling technique. Findings: By using panel regression method, it was found that sukuk negara have positive and significant influence to profitability of sharia banking. Other variables such as FDR, NPF, and BOPO have a negative and significant effect on profitability of sharia banking. CAR did not affect the profitability of sharia banking. Research limitations/implications: The sample of analysis is just 11 general sharia banks in period of 2008-2016. Further research can be completed by using more capital market instruments with the financial performance of both general conventional banking and general sharia banking. Practical implications: It can be implied that there is a positive relationship between the syariah capital market sector and the sharia banking sector. This is a signal for the government to pay more attention to the issuance of sukuk negara with competitive returns in order to improve the financial performance of sharia banking. Originality/value: Sukuk Negara as fiscal and monetary policy instruments have a very important role for the development of sharia banking. This means that the increasing interest of Islamic banking in placing funds in sukuk negara will lead to higher yields also obtained by Islamic banking. Paper type: Research paper Keyword: sukuk negara, financial performance, panel, sharia banking